The Peningkatan Hasil Belajar Peserta Didik Melalui Penerapan Model Pembelajaran Kooperatif Tipe NHT Berbantuan Media Flipchart dengan LKPD Teka-Teki Silang - Tara, Finsensia Marlina; Bano, Vidriana Oktoviana; Ndjoeroemana, Yohana (Pustaka Digital Indonesia, 2025)
Description of the application of the NHT type cooperative learning model with Flipchart media and crossword puzzle LKPD to improve student learning outcomes at SMP N 1 Wewewa Tengah. This research is a Classroom Action Research( CAR) which is carried out in cycles 1 and 2 which include planning, implementation, observation, and reflection. The research subjects are class VII B consisting of 31 students. This study shows that the use of the NHT cooperative learning model supported by Flipchart media and crossword puzzle LKPD can improve student learning outcomes in science lessons at SMP N 1 Wewewa Tengah. The increase was seen during Cycle I and Cycle II, where the increase in learning outcomes in Cycle I reached 68% and in Cycle II increased to 94%. Meanwhile, students affective learning outcomes in Cycle I showed an increase with 14 people getting a very good predicate, 8 people getting a sufficient predicate, and 9 people getting a sufficient predicate. In Cycle II, there were 10 students with excellent grades, 18 with good grades, and 3 with adequate grades. The conclusion is that student learning achievement increased after the implementation of the NHT cooperative learning model supported by flipchart media and crossword puzzle- based worksheets.